Konsep Pendidikan Prenatal dalam Perspektif Tafsir Al-MishbÄh Karya M. Quraish Shihab - Mujahidin, Anwar; Khoiriyah, Zamzam Farrihatul (Taallum: Jurnal Pendidikan Islam, 2018)
This study aims to analyze the tafseer al-MishbÄh by M. Quraish Shihab on the verses relating to the process of the human creation that has relevance to the concept of prenatal education. The approach used in this research is tafsir maudhÅ«i, ie tracing the verses relating to the problem under study and then described the interpretation of the verses. The data that have been collected then analyzed by the method of content analysis which analyze the interpreters thoughts with theoretical categories so that found the main message and the context. The results of the study show that, God created the first human Adam and Eve then cultivate it into human offspring, by creating the womb. The stages of human development in the womb are ranging from nuthfah, alaqah, mudghah and ansyaa khalqan Äkhar. The stage of ansyaa khalqan Äkhar is the stage of the blowing of the spirit, the covenant of God with man, and God gives nature to man. Since that phase, children can get education. The effort to be done by parents in educating children in the prenatal period are running worship, reading and memorizing Al-Qur`a, dzikir, dialogue, follow the study of Islam (majlis ta`lim), behave well, and be consistent.